Mainstreaming Millets: Reviving the Miracle Grain for Addressing Rising Burden of Non-Communicable Diseases - Arunjeet Singh; Jarnail Singh Thakur (Indian Journal of Community Medicine)
Millets have been known and grown in India since the Vedic times and have been part of traditional Indian diets ever since. Production and consumption of millets saw a considerable decline after the Green Revolution. The opportunity cost of substituting wheat and rice with millets is evident now with an incremental increase in the incidence and mortality of non-communicable diseases (NCDs) over successive decades. Food security, climate crisis, and the inherent resilience of the crop to grow in semi-arid climates have been some of the key factors that have been instrumental in reviving the millet story. Millets being rich in micronutrients, fibers, and a low glycemic index are ideally suited to address the rising burden of NCDs. Stewardship by the government in the form of policy inputs and creating a favorable ecosystem with the involvement of farmers, industry, and even consumers to mainstream the grain has seen a paradigm shift in the past decade. 2023 will be observed as the International Year of Millets by the United Nations which will provide the platform to not only advocate the health benefits attributed to the grain but also mainstream millets in the international arena.